Ethical and Political Critique of Violence in Salman Rushdie’s Shalimar the Clown - Sharma, Kamal (Bon Voyage, 2024)
This paper analyses how a benevolent person, who even stands above the petty religious rivalries, becomes ferocious, and cheerfully murders the other due to the unacceptability of otherness of other in the novel Shalimar the Clown by Salman Rushdie. Literature offers insights into death, violence, and mourning in multiple ways. Death is not simply an individual loss; it can widely be understood as a social issue leading to revenge. As a source of revenge, violence appears in terrifying ways. The way death takes place in today’s society helps to blur the notion of what is vulnerability and invulnerability. The risk of being dehumanized in terms of culture, society, religion, and so on emerges against the backdrop of the local and global politics that function through the discourse and powers. The loss of somebody in the life results into aggressive action that appears in violent ways damaging self and other. In the novel, the death of Max Ophuls is planned, designed and performed. It is celebratory for Shalimar where as it counts as grief for India (Daughter) and the world. Drawing on the Butler’s idea of ‘Precarious life’ as well as Care of the Self and Levinas’s idea of Care of the Other, I argue that motive for violence of Shalimar is based on what Butler calls ‘Giving Account to Oneself.’ As this is a qualitative research, I have analyzed the lines extracting them from the primary text, Shalimar the Clown. In the paper, I conclude how person needs to account himself or herself first if the otherness of other (ethics) is not acknowledged.